PENDEKATAN EMOSIONAL DALAM KOMUNIKASI KRISIS: STRATEGI BOEING DALAM MEMBANGUN KEPERCAYAAN DAN PEMULIHAN REPUTASI - Renato Yosia; Ayuningtyas, Fitria (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Effective crisis communication plays a crucial role in reputation recovery and rebuilding public trust. Emotional approaches in crisis communication focus not only on facts but also on addressing the emotions of the public, accelerating the recovery process and reducing uncertainty. This article focuses on the crisis faced by Boeing following the fatal crashes of the 737 MAX aircraft, involving the company’s use of emotional responses in crisis communication. By integrating crisis communication theories such as Situational Crisis Communication Theory (SCCT) and Affective Intelligence Theory, this article analyzes how Boeing managed the crisis through emotional communication strategies and the impact on the company’s reputation. The article highlights the importance of authentic emotional responses in regaining public trust and repairing organizational reputation after a crisis.